The digestive mechanisms of an intertidal grazer, the sea urchin Parechinus angulosus - Sweijd, Neville Anthony (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1991)
Echinoids are important grazers in the near-shore ecosystem and can significantly effect their ecology. The sea urchin Parechinus angulosus occurs inter- and subtidally along the southern African coast. Within this range it consumes an extremely wide variety of algae. Since algal cell walls have an almost species specific chemical composition, the question arises as to how it can digest the algae that it consumes. In order to investigate the digestive mechanisms employed by P. angulosus, an ultrastructural study of the gut was undertaken to characterize the tissue and identify functional regions in the gut. Ten structural and storage polysaccharides commonly found in macroalgae were used as substrates to assay the digestive polysaccharidases of the sea urchin. The enteric bacteria of the sea urchin were isolated and tested separately for polysaccharidase activity using the same substrates. The results shown that the gut of Parechinus angulosus is regionally specialized, with the foregut primarily responsible for the production of hydrolytic enzymes, while the hindgut is primarily absorptive. The occurrence of lamellar bodies, heterolysosomes, cytoplasmic blebs and paddle cilia among other characteristic features of the digestive epithelium are described and discussed. Two levels of enzyme activity are apparent. Generally the urchin could hydrolyze the reserve polysaccharides, but only partially hydrolyze the structural polysaccharides, of red and green algae. P.angulosus was unable to digest alginic acid, the main structural polysaccharide of brown algae. Mixed cultures of bacteria utilized only the reserve polysaccharides of red and green algae. Significantly, the bacteria were able to hydrolyze alginic acid. Enteric bacteria also showed agarolytic activity. Parechinus angulosus has the ability to digest red and green algae. No lysozyme activity was detected. The enteric bacteria can digest the same algal reserve polysaccharides and so may compete for carbon in the gut. However, in the case of brown algae, bacteria have a potentially important endosymbiotic role as agents of digestion. These results correspond with food preference studies which have shown that, although P.angulosus consumes the kelp Ecklonia maxima, in the western Cape, it is amongst its least preferred food species. The reasons for this are its unpalatability and the urchin's inability to digest brown algae. The digestibility of algal material can be an important factor in determining algal-herbivore interactions.
Keywords: Sea urchins -- Nutrition; Sea urchins; Echinoida